Climate protection as an opportunity for banks to increase earnings and consumer trust - Kiszka, Sabrina; Hastenteufel, Jessica (Managerial Economics, 2021)
Banks are currently facing numerous challenges. In addition to the ongoing cheap money policy of the European Central Bank, a regulated market environment and a rapidly progressive digitization, financial institutions are increasingly confronted with topics such as sustainability and climate protection. From the latter derive not only risks but also chances for banks. Sustainability risks can impact different risk categories such as market risks, credit risks, operational risks, and liquidity risks. Moreover, reputational risks can occur in this context. This is especially important as bank customers constantly develop a greater awareness of ecological issues, and thus, develop increasing expectations on how companies – like banks – deal with issues like climate protection and sustainability. For this reason, we will start with a theoretical explanation of the key words and then present the results of our customer survey to highlight the current expectations of bank customers in the context of climate protection. Based on this, we formulate recommendations for banks on how to generate a competitive advantage by engaging in climate protection and by taking sustainable actions.